Analysis of United States Quantitative Easing Policy on Real Output in Indonesia - Viphindrartin, Sebastiana; Yunitasari, Duwi; Wilantari, Regina Niken (Journal of Indonesian Applied Economics, 2021)
This study discusses analysis of United States quantitative easing policy on real output in Indonesia. QE policy not only affects US economy but also influences the economic indicators of other countries, especially Indonesia countries with increasingly integrated market conditions. At present the Indonesia economy has been very open, so that policies originating from abroad can affect the country's economic conditions. The possibility of global spillover against non-conventional monetary policies such as QE. It is using the Vector Autoreggresion (VAR) methods to see the effect of QE policy. The data is time series for the 1999Q1-2016Q4. This study will analyze the impact of macroeconomic variables such as interest rates, money supply and inflation on GDP. The results of this study indicate that the implementation of the QE policy has an impact on the rate of GDP growth in each country of Â Indonesia.Â